2022
DOI: 10.1155/2022/5791915
|View full text |Cite
|
Sign up to set email alerts
|

MFG-E8 Knockout Aggravated Nonalcoholic Steatohepatitis by Promoting the Activation of TLR4/NF-κB Signaling in Mice

Abstract: Nonalcoholic steatohepatitis (NASH) is the common liver disease characterized by hepatic steatosis, inflammation, and fibrosis; there are no approved drugs to treat this disease because of incomplete understanding of pathophysiological mechanisms of NASH. Milk fat globule-epidermal growth factor-factor 8 (MFG-E8), a multifunctional glycoprotein, has shown anti-inflammation and antifibrosis. Here, MFG-E8 was shown to play a key role in NASH progression. Using methionine and choline deficient (MCD) diet-fed mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Liver injury may retain the active surface of HSCs and accelerate the migration of inflammatory cells to the injured liver, secreting a significant number of inflammatory mediators such as TNF- α , IL-6, and IL-1 β to enhance the development of liver fibrosis [ 10 12 , 40 , 41 ]. TAK-242 was also observed to reduce the incidence of liver inflammation and fibrosis in Hu et al's research [ 42 ]. Similarly, the current research found that TAK-242 lowered the levels of inflammatory factors IL-1 β , IL-6, and TNF- α in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Liver injury may retain the active surface of HSCs and accelerate the migration of inflammatory cells to the injured liver, secreting a significant number of inflammatory mediators such as TNF- α , IL-6, and IL-1 β to enhance the development of liver fibrosis [ 10 12 , 40 , 41 ]. TAK-242 was also observed to reduce the incidence of liver inflammation and fibrosis in Hu et al's research [ 42 ]. Similarly, the current research found that TAK-242 lowered the levels of inflammatory factors IL-1 β , IL-6, and TNF- α in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…further found that it plays a vital role in the process of non-alcoholic steatohepatitis (NASH). When MFG-E8 is knocked down, liver steatosis and lipid accumulation are aggravated, and fibrosis is promoted, confirming that this is related to the activation of the TLR4/NF-κB signalling pathway after the knockdown of MFG-E8 [ 35 ]. Sodium-glucose cotransporter 2 (SGLT2) inhibitors can improve hepatic steatosis and fibrosis in patients with chronic liver disease.…”
Section: Liver Microenvironment and Liver Fibrosismentioning
confidence: 91%
“…Joints from mice were fixed in 4% PFA for 14 h and decalcified in 14% EDTA for 3 d. Furthermore, the cartilage from human was also fixed in 4% PFA for 16 h and decalcified in 14% EDTA for 5 d. Afterward, the joints and cartilage were preserved in an optimum cutting temperature (OCT) compound, cut to a thickness of 10μm, and subjected to immunofluorescence using antibodies recognizing Toll-like receptor 7 (Boster, China, 1:100).The immunofluorescence protocol can be found in our previously published article. 26 …”
Section: Methodsmentioning
confidence: 99%
“…The process of mRNA and cDNA was conducted following the previously described method. 26 Primers of interest genes were designed using NCBI Primer-Blast software. Primer sequences in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%